The scientometric evaluation of the institutional research: The Marmara Universities-Part 4 - Konur, Özcan (SILA SCIENCE, 2013)
The scientometric analysis of the research has become one of the most used methods to assess the research performance of the scholars, departments, faculties, universities, countries, and journals at a global scale in recent years. However, there has not been an extensive scientometric evaluation of the institutional research carried out by the universities in the Marmara Region of Turkey, to examine the development of the research over time. Hence, the purpose of this study was to carry out a scientometric evaluation of the research performed by these universities using three indices in a series of four papers. In the final part of these serial papers, it was found that the most collaborating country was the US and the extent of the overseas collaboration was substantial whilst TUBITAK and University of California System were the most prolific collaborated institutions. 97% of these papers were written in English, followed by the low-impact Turkish papers. The research output spectacularly increased over time starting with two papers in 1952 and 1954 reaching a peak with 6,640 papers in 2011. The number of papers comprised 0.6%, 2.1%, 11.0%, 58.9%, and 29.0% of the regional research output for the periods of 1946-1979, 1980-1989, 1990-1999, 2000-2009, and 2010-2012, respectively. It was hypothesized that the key driver for the research output growth was the huge higher education spending in the first place. Indeed, the numbers of the academic force increased in recent years from 5,147 in 1995 to 13,953 in 2010 with 171% increase with differential increase rate for the state and foundation universities. "Water Sci. & Technol." was the most publishing journal, followed by "J. Appl. Polym. Sci.". The subject category with the highest degree of citation impact was Engineering, followed by Chemistry. The research productivity of the Medical Faculties was behind the Faculties of Engineering and Natural Sciences. The Natural and Applied Sciences dominated both the most prolific journals and most prolific subject categories lists in contrast to Social Sciences and Humanities & Arts. A paper on ZnO materials and devices was the most cited paper with 2,868 citations and the most cited paper list was dominated by the Natural and Applied Sciences and the top universities. A paper on the European guidelines on hypertension management was the hottest paper with 393 citations and the Natural and Applied Sciences and the top universities dominated the hottest papers list too. The results of the final part in the serial papers suggest that there was a close structureresearch performance relationships for these universities hinting the strong effect of the formal and informal rules adapted by these universities on their respective research productivity following North's new institutional theoretical framework
Keywords: Web of Knowledge; Turkey; SSCI; AandHCI; Marmara Universities; Scientometrics; SCIE; Research productivity; Higher education spending